2012
DOI: 10.1371/journal.pone.0028249
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Adjunctive Family Therapy and Treatment as Usual Following Inpatient Treatment for Anorexia Nervosa Adolescents

Abstract: Research on treatments in anorexia nervosa (AN) is scarce. Although most of the therapeutic programs used in ‘real world practice’ in AN treatment resort to multidisciplinary approaches, they have rarely been evaluated.ObjectiveTo compare two multidimensional post-hospitalization outpatients treatment programs for adolescents with severe AN: Treatment as Usual (TAU) versus this treatment plus family therapy (TAU+FT).MethodSixty female AN adolescents, aged 13 to 19 years, were included in a randomized parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(134 citation statements)
references
References 48 publications
4
127
1
2
Order By: Relevance
“…The second one is a more integrative long-term systemic model which can be adapted to different contexts of care (inpatient, outpatient, day care). To the extent that FBT has demonstrated its effectiveness in several RCTs, in contrast to the systemic family therapy model for which the evidence base remains scarce and preliminary in the field of ED [73,74], it has been somewhat prematurely concluded that FBT is the best evidencebased treatment for ED children and adolescents. In a recent RCT, Agras et al [75] showed that there were no significant differences in the outcome of single FBT and single systemic family therapy (SyF) at the end of treatment and at one-year follow-up, for an adolescent ED population.…”
Section: Discussionmentioning
confidence: 99%
“…The second one is a more integrative long-term systemic model which can be adapted to different contexts of care (inpatient, outpatient, day care). To the extent that FBT has demonstrated its effectiveness in several RCTs, in contrast to the systemic family therapy model for which the evidence base remains scarce and preliminary in the field of ED [73,74], it has been somewhat prematurely concluded that FBT is the best evidencebased treatment for ED children and adolescents. In a recent RCT, Agras et al [75] showed that there were no significant differences in the outcome of single FBT and single systemic family therapy (SyF) at the end of treatment and at one-year follow-up, for an adolescent ED population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to inclusion in the study, all participants were hospitalized in our care unit for a life-threatening physical and/or mental state (for one or more of the following criteria: BMI below 14 and or rapid weight loss and/or compromised vital functions, severe depression, high suicide risk, chronic under-nutrition with low weight, and failure of out-patient care) according to international guidelines [7,34,35,36]. Once the patient was admitted, the objectives of hospitalization were defined by means of a weight contract establishing a discharge target weight [36,37,38].…”
Section: Methodsmentioning
confidence: 99%
“…Out of the 76 eligible participants, 16 refused to participate (21%). The patients and parents who refused to participate did not differ from those included with regard to sociodemographic variables or clinical status on entry or at discharge (data available on request) [34]. The evaluations were conducted during the second part of the hospitalization, when refeeding was partially achieved and the patient was in regular contact with the family.…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that focusing on the intrafamilial dynamic improves treatment effectiveness in severe AN patients even after 13 years follow up. 84 …”
Section: Family-based Treatment (Fbt)mentioning
confidence: 99%